Pemanfaatan Daun Kelor (Moringa oleifera) dalam Fortifikasi Pembuatan Nugget - Z. Suhaemi; Husmaini; E. Yerizal; N. Yessirita (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
The aimed of this study was to determine the effect of Moringa Leaf Flour (MLF) on chicken and duckmeat processed quality formed nugget as fortification. Duck meat has advantages with mineral content,especially iron, about 50% of the daily needs for adult’s body compared to chicken meat which is only9%. Duck meat also contains high levels of vitamins B, C and antioxidants, but chicken meat neither.This study was conducted in two stages, the first was nugget experiment with chicken meat, and thesecond stages with duck meat. The meat used were ground with flour and seasoning. The variablesmeasured were the nutritional content which includes crude protein and fat, also cholesterol total, theother variables were sensory evaluation which include scale of taste, texture and color. This study usedcompletely randomized design with 4 treatments addition of MLF (0.0%; 0.5%; 1.0% and 1.5%), eachtreatments replicated 5 times. The result show that the more addition of MLF will increased CrudeProtein and highly significant decreased crude fat and cholesterol total. In the other hand, addition ofMLF was highly significant lowering the taste, texture and color of nugget, but still in acceptable range.